Kualitas Tes dan Hasil Belajar Matematika Siswa Kelas VIII SMP Negeri 9 Banda Aceh Tahun Pelajaran 2011/2012 - . Suryawati; . Yulfikar (Jurnal Peluang, 2012)
AbstractThis research related to the quality of the test and math learning outcomes, conducted at SMP Negeri 9 Banda Aceh entitled "Quality of test and the mathematics learning outcomes Class VIII SMP Negeri 9 Banda Aceh Academic Year 2011/2012”. The aim is to figure out the learning outcomes and the quality of math test of students grade VIII SMP Negeri 1 Banda Aceh Academic Year 2011/2012. Quality of test includes the analysis of validity, reliability, difficulty level, item discrimination and distractor analysis. The population in this research is all student class VIII consists of VIII-1 with 21 students, class VIII-2 with 21 students, class VIII-3 with 21 students and class VIII-4 with 19 students. The total samples are 82 students with the number of multiple choice test is 25 questions and 5 questions of essay.  Data collections in this research by using documentation technique, by checking the students answer sheet in even semester examination academic year 2011/2012. The results shows that (1) the validity of multiples choice questions was low and sufficient for essay, (2) the reliability of multiples choice and essay were good enough, (3) difficulty level of the multiple choice and essay questions were good enough, (4) item discrimination of multiple choice questions still low but the essay questions in good categorize for 60% and bad for 40%. The quality of mathematics test in SMP Negeri 9 Banda Aceh is low for multiple choice questions and sufficient for essay. Thus we can conclude the analysis of learning outcomes data grade VIII SMP 9 Banda Aceh in the classical mastery learning achievement is only 3.66%. In this case we can conclude that the classical mastery learning is very low (not complete).  Key Words: Quality of test and math learning outcomes